2015
DOI: 10.1097/acm.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Intervention to Break the Gender Bias Habit for Faculty at One Institution

Abstract: Purpose Despite sincere commitment to egalitarian, meritocratic principles, subtle gender bias persists, constraining women’s opportunities for academic advancement. The authors implemented a pair-matched, single-blind, cluster-randomized, controlled study of a gender bias habit-changing intervention at a large public university. Method Participants were faculty in 92 departments or divisions at the University of Wisconsin-Madison. Between September 2010 and March 2012, experimental departments were offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
391
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 435 publications
(419 citation statements)
references
References 66 publications
9
391
2
5
Order By: Relevance
“…28 A recent study found that a 20-minute workshop on implicit biases and strategies for overcoming them changed participants' perceptions of bias. 29 Furthermore, a randomized trial involving faculty from 92 departments at 1 university showed an increase in self efficacy to engage in gender-equity-promoting behaviours after a 2.5-hour workshop 30 .…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent study found that a 20-minute workshop on implicit biases and strategies for overcoming them changed participants' perceptions of bias. 29 Furthermore, a randomized trial involving faculty from 92 departments at 1 university showed an increase in self efficacy to engage in gender-equity-promoting behaviours after a 2.5-hour workshop 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The NIH's Enhancing Diversity initiative addresses explicitly two factors that we know affect career entry, retention, and advancement: unconscious bias and stereotype threat. Although unconscious biases may lead scientists to make flawed decisions about hiring (20), scientifically sound data support the efficacy of interventions to mitigate bias (21,22). Stereotypes that alter an individual's sense of belonging in science can impede performance (23,24), but we have strong evidence from a randomized controlled trial of undergraduates that interventions can overcome these untoward effects (25).…”
Section: Challenge 3: Identifying Psychological and Social Factors Thmentioning
confidence: 99%
“…Such a study would have the potential to identify when explicit and implicit biases begin to emerge and whether they increase with tenure in a male-dominated field. Additionally, these studies could focus on working to diminish felt threat among this specific group of men through bias workshops, which have had success reducing harassment long-term in recent research (Carnes et al 2015;Fine et al 2014).…”
Section: Future Researchmentioning
confidence: 99%